Sosialisasi Kesiapsiagaan Gempa Bumi sebagai Upaya Mitigasi Bencana di Desa Jembatan Kembar Timur Kabupaten Lombok Barat - Saidah, Humairo; Muhajirah; Wiradarma, Lalu Wirahman; Rohani; Hasyim; Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya; Yasa, I Wayan; Supriyadi, Anid (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
East Jembatan Kembar Village is located in an earthquake-prone area in West Lombok Regency, making it essential to enhance community capacity in disaster preparedness. This outreach activity aimed to increase community awareness of earthquake preparedness and to initiate the formation of a community-based structure capable of acting during emergencies. The method used included face-to-face counseling and participatory discussions involving the village head, village staff, community leaders, youth, and local residents. Topics covered included basic knowledge of earthquakes, appropriate actions before, during, and after an earthquake, and the importance of forming a Community Disaster Resilience Group (KMTB). Although the activity was conducted in the morning and received enthusiastic support from the village government, public participation was limited due to time constraints with residents' daily work routines. Nevertheless, the activity successfully delivered key information to attendees and led to the formation of the Community Disaster Resilience Group as a continuation of the program. This group is recommended for immediate formalization by the village government so that it can establish statutes and bylaws, build cross-sector coordination, and fulfill its role in preparedness and emergency response. The results demonstrate that collaborative efforts between local authorities and communities can be an effective strategy for building village resilience to disasters.